2015
DOI: 10.1016/j.foodres.2015.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Quality changes of pasteurised mango juice during storage. Part I: Selecting shelf-life markers by integration of a targeted and untargeted multivariate approach

Abstract: For the first time, a multivariate approach combining targeted and untargeted data was used to obtain insight into quality changes in pasteurised mango juice (cv. 'Totapuri') as a function of storage (42 °C for 8 weeks). Mango juice samples were formulated with addition of different potential precursors for different quality-related chemical reactions: ascorbic acid, citric acid and sugars. Control (diluted mango puree with water), ascorbic acid-enriched (AA 250 and AA 500 ), citric acid-enriched (CA, CA+AA 25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 70 publications
0
13
0
5
Order By: Relevance
“…The vitamin C loss at the end of the storage period was 50%, 37%, and 45% for untreated, pasteurized, and ozonized juices, respectively. Wibowo, Grauwet, Gedefa, et al () also observed a decrease in AA concentration during the storage of ozonized mango juice. This degradation can be attributed to the dissolved oxygen in the juice and the one present in the headspace in the early stages of storage (Torres et al, ).…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…The vitamin C loss at the end of the storage period was 50%, 37%, and 45% for untreated, pasteurized, and ozonized juices, respectively. Wibowo, Grauwet, Gedefa, et al () also observed a decrease in AA concentration during the storage of ozonized mango juice. This degradation can be attributed to the dissolved oxygen in the juice and the one present in the headspace in the early stages of storage (Torres et al, ).…”
Section: Resultsmentioning
confidence: 83%
“…Regarding pH behavior (Figure b), a significant increase was observed for untreated samples, while in treated juices this parameter was maintained almost constant during all storage periods. Although contradictory results were found in the literature (Rabie et al, ; Zahid et al, ), some works also reported no significant differences in the pH of ozonized and pasteurized fruit juices along storage (Mena et al, ; Vegara, Martín, Mena, Saura, & Valero, ; Wibowo, Grauwet, Gedefa, Hendrickx, & Loey, ).…”
Section: Resultsmentioning
confidence: 95%
“…According to other studies, the loss of colour in non-treated MJ might be related with the oxidative reactions mostly triggered by residual activity of POD and PPO (Timmermans et al 2011;Wibowo et al 2015). In this sense, the increase of RA POD observed in non-treated MJ probably conducted the deterioration of colour.…”
Section: Physicochemical Parametersmentioning
confidence: 78%
“…On one hand, thermal treatment is commonly used in the juice industry because of its well-known effectiveness in the inactivation of microorganisms and quality-degrading enzymes (Mercadante and Rodriguez-Amaya 1998;Soliva-Fortuny et al 2009). However, undesired chemical, physical and sensorial changes as well as reduction of bioactive compounds content have been observed in thermally-treated juices (Sánchez-Moreno et al 2005;Wibowo et al 2015). On the other hand, non-thermal treatments allow to obtain microbiologically stable fruit juices but also a better preservation of sensorial and nutritional characteristics than conventional treatments (Chen et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…El mango (Mangifera indica L.) es uno de los frutos tropicales más importantes producidos en el mundo según la Organización para la Agricultura y la Alimentación (fao 2015;Wibowo et al 2015a;2015b). En Colombia se producen actualmente más de 270 mil toneladas de mango al año (fao 2015), lo que representa aproximadamente cerca del 0,8 % de la producción agrícola del país (Agronet 2015).…”
Section: Introductionunclassified